Design and Validation of Media Literacy Education Model in Education: A Qualitative Study - Ali Davarpanah; Nader Shahamat; Reza Zarei; Ebadollah Ahmadi (Iranian Journal of Educational Research)
Objective: The current study was carried out with the objective of formulating and validating the media literacy instructional model within the educational framework. Methods: Employing a qualitative exploratory approach, this study utilized purposeful sampling and criteria-based techniques for sample selection. Data collection involved semi-structured interviews during field research and examination of primary documents and educational materials in the library. Theoretical saturation was reached after interviewing 20 individuals, with data analysis conducted through thematic analysis. Following validation and alignment with existing theoretical frameworks and literature, expert opinions were sought regarding the scope and elements of media literacy education. Results: The findings facilitated the identification of 49 elements distributed across 6 dimensions: media literacy instructors, educational practices, curriculum development, school environment, governmental involvement, and Ministry of Education contributions. Conclusions: Overall, the results offer valuable insights for educational policymakers aiming to enhance media literacy within the realm of Education.